Effects of waste-based concentrates from broiler farm on physico-chemical qualities and blood profile of landrace pigs - Ariana, Tirta; Kisworo, Djoko; Bulkaini, Bulkaini; Miwada, Sumerta; Warmadewi, Dewi Ayu; Putri, Rahayu Tanama (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The study aimed to determine the effect of giving concentrate protein from closed house (CP-CH) broiler farm waste in rations on the meat quality (physical-chemical) and blood profile of landrace crossbreed pigs. Materials and Methods: The study used a completely randomized design (CRD) with 3 treatments and 4 replications with 12 finisher-phase landrace pigs with an average body weight of 63.42 ± 2.39 kg. The treatments were: A (control): use of 0% CP-CH + 24% CP-152 concentrate; B: 12% CP-CH + 12% CP-152 concentrate; and C: 24% CP-CH + 0% CP-152 concentrate. The research parameters were meat quality (physical-chemical meat) and blood lipid profile [total cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), and triglycerides (TGs)]. Results: The results showed that treatment group B obtained physical meat quality (pH, drip loss, cooking loss, and water holding capacity) and meat chemical quality (moisture, protein, fat, and ash content) that were almost the same as the control (p > 0.05). By administering 24% CP-CH + 0% CP-152 (C) concentrate, there was a significant decrease in the physical and chemical quality of crossbreed landrace pigs (p < 0.05). Administration of CP-CH at 12%–24% did not affect total cholesterol, HDL, LDL, or blood TGs in landrace-crossbreed pigs. Conclusion: Giving 12% CP-CH (B) obtained meat quality (physical and chemical) almost the same as the control group. Treatment group C significantly reduced the physical and chemical quality of the meat. Administration of CP-CH at 12%–24% did not affect the blood profile of landrace crosses. J. Adv. Vet. Anim. Res., 10(4): 579–586, December 2023 http://doi.org/10.5455/javar.2023.j712